Efficacy of biofilm decontamination methods of dental implant surfaces: A systematic review of in vitro studies - Abushahba, Faleh; Algahawi, Ahmed; Areid, Nagat; Vallittu, Pekka K.; Närhi, Timo (Wiley, 2026)
This systematic review examines the decontamination techniques used to clean titanium (Ti) implant surfaces covered with in vitro bacterial biofilms. The selected studies were gathered from the PubMed and Web of Science databases. These include in vitro studies investigating decontamination methods used to clean Ti implant surfaces coated with bacterial biofilms until January 2024. The determined studies were filtered according to the PRISMA guidelines, and the Science in Risk Assessment and Policy (SciRAP) was used to assess the reporting and methodological quality of the included studies. A total of 634 full-length peer-reviewed articles were identified. After excluding duplicate papers between the databases and screening according to the predefined inclusion and exclusion criteria, 13 studies were included. The decontamination methods investigated included mechanical, chemical, and physical methods, either as a single or in a combined approach. Significant variability was observed among the included studies. Combining the mechanical and physical methods with a chemical yielded the most significant reduction in both single- and multiple-species biofilms. The current results do not indicate that any single decontamination technique is more effective than others in eradicating bacterial biofilm from Ti surfaces; the combined approach was more advantageous than the single ones.